2014
DOI: 10.1093/brain/awu178
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition and serotonin in autism: a functional MRI study using acute tryptophan depletion

Abstract: Stereotyped, repetitive behaviours in autism may reflect deficits in serotonin-modulated inhibitory control. Daly et al. use fMRI to compare the effects of acute tryptophan depletion in adult males with autism and controls performing the Go/No-Go task. Opposite effects are seen in the two groups, consistent with altered inhibition in autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 59 publications
5
61
0
Order By: Relevance
“…The amounts used are standard for ATD studies (e.g. Evers et al ., ; Fusar‐Poli et al ., ; Bilderbeck et al ., ; Daly et al ., , ). The total protein of the TRP‐ drink was 82.1 g. The amount of each amino acid contained in the TRP‐ drink was l ‐Alanine, 4.4 g; l ‐Arginine 3.9 g; l ‐Cystine, 2.2 g; Glycine, 2.6 g; l ‐Histidine, 2.6 g; l ‐Isoleucine, 6.4 g; l ‐Leucine, 10.8 g; l ‐Lysine monohydrochloride, 8.8 g; l ‐Methionine, 2.4 g; l ‐Phenylalanine, 4.6 g; l ‐Proline, 9.8 g; l ‐Serine, 5.5 g; l ‐Threonine, 5.5 g; l ‐Tyrosine, 5.5 g; l ‐Valine, 7.1 g. The TRP+ drink was the same as the TRP‐ drink, with the addition of 1.8 g l ‐Tryptophan.…”
Section: Methodsmentioning
confidence: 99%
“…The amounts used are standard for ATD studies (e.g. Evers et al ., ; Fusar‐Poli et al ., ; Bilderbeck et al ., ; Daly et al ., , ). The total protein of the TRP‐ drink was 82.1 g. The amount of each amino acid contained in the TRP‐ drink was l ‐Alanine, 4.4 g; l ‐Arginine 3.9 g; l ‐Cystine, 2.2 g; Glycine, 2.6 g; l ‐Histidine, 2.6 g; l ‐Isoleucine, 6.4 g; l ‐Leucine, 10.8 g; l ‐Lysine monohydrochloride, 8.8 g; l ‐Methionine, 2.4 g; l ‐Phenylalanine, 4.6 g; l ‐Proline, 9.8 g; l ‐Serine, 5.5 g; l ‐Threonine, 5.5 g; l ‐Tyrosine, 5.5 g; l ‐Valine, 7.1 g. The TRP+ drink was the same as the TRP‐ drink, with the addition of 1.8 g l ‐Tryptophan.…”
Section: Methodsmentioning
confidence: 99%
“…Tryptophan depletion, which is expected to cause decreased synaptic 5-HT, leads to worsened repetitive behaviors and irritability in autism (McDougle et al, 1993, McDougle et al, 1996). Neuroimaging studies show differential effects of tryptophan depletion on brain region activity by fMRI in the ASD population in contrast to typical controls, particularly in response to presentation of emotional faces (Daly et al, 2012, Daly et al, 2014). Adult studies suggested that serotonin reuptake inhibitors relieve symptoms of irritability and rigid-compulsive behavior in autism (Gordon et al, 1993, Hollander et al, 2005, Hollander et al, 2012); however studies in children have been less supportive, perhaps because of greater adverse events in children or because of methodological difficulties (King et al, 2009, King et al, 2013).…”
Section: The Central Serotonin System In Autism Spectrum Disordermentioning
confidence: 99%
“…7 Serotonin plays a substantial role in abnormal inhibitory networks in autism. 11 The plasma level of tryptophan, which is a precursor for serotonin synthesis, is decreased in autism. 12 Moreover, supplementation with tryptophan as a precursor of serotonin is supposed to be effective for autism prevention.…”
Section: Introductionmentioning
confidence: 99%